Product Development of High Carotenoids Chocolate Confectionery Based on Red Palm Olein Oleogel - Tria Amanda; Nur Wulandari; Dase Hunaefi (The University of Lampung, 2025)
Red palm oil (RPO)-based oleogel had potential as a substitute for cocoa butter substitute (CBS) in the manufacture of chocolate confectionery. This study aimed to obtain the optimum formula of chocolate confectionery with RPO-based oleogel and determine the physicochemical characteristics, sensory profile and hedonic rating, nutrition facts, and contribution to meet the vitamin A requirement. The methods used were: (1) manufacture and characterization of RPO-based oleogel, (2) optimization formulas of chocolate confectionery with RPO-based oleogel by D-optimal mixture design, and (3) characterization of chocolate confectionery with RPO-based oleogel. The result showed that RPO-based oleogel had a high carotenoid content of 545.87±3.39 mg/kg and slip melting point of 46.67‒47.83°C. The optimum formula was 17.780% CBS, 13.880% RPO-based oleogel, and 3.340% stearin which had a texture of 1861.49 gf and total carotenoids of 207.861 mg/kg. The sensory profile of chocolate confectionery with RPO-based oleogel based on the RATA method was yellow color; sweet, milk, fatty, and vanilla flavor; sweet, bitter, and fatty aftertaste; hard texture; melted, sandy, and sticky mouthfeel. The score of children panelists’ liking was 4.52 (liked extremely). One serving size of this product fulfilled 12% of the daily vitamin A requirement from the total requirement of 600 RE.